2001
DOI: 10.1086/321516
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter Imaging Polarimetry of the NGC 7538 Region

Abstract: Imaging polarimetry of the 850 km continuum emission in the NGC 7538 region, obtained with the SCUBA Polarimeter, is presented. The polarization map is interpreted in terms of thermal radiation by magnetically aligned dust grains. Two prominent cores associated with IRS 1 and IRS 11, IRS 1(SMM), and IRS 11(SMM), are found in the surface brightness map. Although these cores look similar in surface brightness, their polarization shows striking di †erences. In IRS 11(SMM), the polarization vectors are extremely w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…The apparant curvature of the field and the manner in which the field aligns with the velocity gradient in the CS bridge can be interpreted as evidence that the magnetic field is being shaped by the pressure and dynamics of the gas. Similar magnetic field behaviour has been seen in recent SCUBA polarimetry of NGC 7538 (Momose et al 2001) where the blueand red-shifted outflow lobes from IRS11 are observed to have quite a high degree of curvature. The magnetic field inferred from the polarimetry follows the same curvature.…”
Section: The Magnetic Field In W51a: Just How Important Is It?supporting
confidence: 84%
See 2 more Smart Citations
“…The apparant curvature of the field and the manner in which the field aligns with the velocity gradient in the CS bridge can be interpreted as evidence that the magnetic field is being shaped by the pressure and dynamics of the gas. Similar magnetic field behaviour has been seen in recent SCUBA polarimetry of NGC 7538 (Momose et al 2001) where the blueand red-shifted outflow lobes from IRS11 are observed to have quite a high degree of curvature. The magnetic field inferred from the polarimetry follows the same curvature.…”
Section: The Magnetic Field In W51a: Just How Important Is It?supporting
confidence: 84%
“…We choose to briefly discuss these features here because simulations do show that such polarisation patterns are possible for pinched and twisted field morphologies (Aitken et al 2001) as well as for helical fields (Fiege & Pudritz 2000), although the latter deals with linear structures and is not really applicable to discrete sources. Furthermore, such "submillimetre polarisation nulls" either side of a bright core have been previously observed towards NGC7538 IRS1 (Momose et al 2001). In both of these cases, the field pattern appears very much like the familiar polarisation disks seen in scattered light, at nearinfrared and optical wavelengths, around sources with optically thick disks (e.g.…”
Section: Submillimetre Polarimetrymentioning
confidence: 56%
See 1 more Smart Citation
“…Although the polarization vectors are locally disturbed, at an angular resolution of 14 arcsec the magnetic field directions agree with the direction of the outflow (Momose et al 2001), while at milliarcsecond (mas) resolution the OH maser observations indicate a magnetic field oriented orthogonal to the outflow (Hutawarakorn & Cohen 2003). Because H 2 O and CH 3 OH masers were detected close to the center of the continuum emission, i.e.…”
Section: Introductionmentioning
confidence: 73%
“…In order to assess this hypothesis on planetary evolution, it is necessary to carry out high-spatial-resolution polarimetery mapping (about 1 AU). Near infrared (Lucas et al, 2004) and sub-millimeter (Tamura et al, 1999) imaging polarimetry was recently reported for YSO regions as well as for massive young objects (Momose et al, 2001). Spatial resolutions in these observations were about 100 AU although the data indicate that partial magnetic alignment of dust particles does take place in these systems.…”
Section: Conditions Required To Reproduce Dust Alignment In Planetarymentioning
confidence: 90%